Ten moonstruck piglets - Johnson, Lindsay Lee.; Cneut, Carll (Boston : Clarion Books, 2011)
On the night of the full moon, ten piglets go out adventuring while their mother is fast asleep.
Kirkus Review
Publisher's Weekly
Kirkus Review, March 2011
Publisher's Weekly, February 2011
3.1
K-3
Keywords: Piglets -- Juvenile fiction; Stories in rhyme; Animals -- Infancy -- Fiction; Pigs -- Fiction; Stories in rhyme; Animal babies -- Fiction; Pigs -- Fiction; Stories in rhyme; Picture books for children